Efficacy of ImageJ in the assessment of apoptosis - Helmy Iman M; Abdel Azim Adel M (BMC, 2012)
Abstract Objective To verify the efficacy of ImageJ 1.43 n in determining the extent of apoptosis which is a complex and multistep process. Study Design Cisplatin in different concentrations was used to induce apoptosis in cultured Hep2 cells. Cell viability assay and nuclear image analysis of stained Hep2 cells were used to discriminate apoptotic cells and cells suspected to be undergoing apoptosis from control cells based on parameters such as nuclear area, circularity, perimeter and nuclear area factor (NAF), in association with visual morphology. Results Image analysis revealed a progressive and highly significant decrease in nuclear area factor detected in apoptotic cells and in cells suspected of undergoing apoptosis compared to the control cells (P-values < 0.01). Some of the other studied parameters showed also the same trend. This decrease was assumed to indicate DNA loss. Image analysis results correlated positively and significantly with the results obtained by cell viability assay (R = 0.958, P-value = 0.042). NAF was the most reliable parameter in assessment of apoptosis. Conclusion Nuclear area factor can be calculated using powerful free and open-source software. Consequently, a quantitative measure of apoptosis can be obtained that is linked to morphological changes. ImageJ 1.43 n may therefore provide a useful tool for the assessment and discrimination of apoptotic cells. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/5929043086367338